Antioxidant potential of wine polyphenols on hematological indices and apical periodontitis in male rats - de Oliveira SALES-JUNIOR, Romulo [UNESP]; ALVARADO, Julissa Denisse Arguello [UNESP]; de Moura PEREIRA, Bharbara [UNESP]; RICCI, Rafaela [UNESP]; da Silva MACHADO, Nathália Evelyn [UNESP]; FERRAZ, Murilo Catelani [UNESP]; de FREITAS, Rayara Nogueira [UNESP]; BARZOTTI, Renan Jose [UNESP]; Chaves Neto, Antonio Hernandes [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2025)
OBJECTIVE: To investigate the effects of dealcoholized red wine supplementation on blood cells and the redox state in male rats with established apical periodontitis (AP). METHODOLOGY: Thirty-two male Wistar rats were assigned to one of four groups: control (C), dealcoholized red wine (DRW), red wine (RW), and alcohol (AL). AP was induced, and supplementation was administered for 30 days, starting 30 days after AP induction. At the end of the 60th day, the maxillae were removed for AP radiographic analysis and blood was collected for blood cell and redox state analysis. Statistical tests were applied (p<0.05). RESULTS: The C and DRW groups showed higher weight gain percentages (p<0.05). The DRW and AL groups exhibited the smallest and the largest periapical lesion areas, respectively (p<0.05). The RW and DRW groups showed similar red blood cell parameters to the C group but different from the AL group (p<0.05). Lymphocyte counts were smaller in the DRW and RW groups compared to the AL and C groups (p<0.05), and the neutrophil count was lower in the AL group (p<0.05). No significant differences were found in monocytes and in lipid and protein oxidative damage. Superoxide dismutase activity was lower in the AL group (p<0.05). The DRW group presented a higher glutathione concentration compared to the RW and AL groups (p<0.05). CONCLUSION: DRW reduced periapical lesion size and altered the blood profile by reducing the lymphocyte count and increasing the concentration of endogenous antioxidants such as GSH in male rats with established AP.